A Guided Problem‐Based Learning (PBL) Approach: Impact on Critical Thinking. (April 2014) - Nargundkar, Satish; Samaddar, Subhashish; Mukhopadhyay, Somnath
ABSTRACT The impact of the Guided Problem Based Learning (Guided PBL) approach on Critical Thinking (CT) skills in a core business analysis course was examined. The implementation of this approach included using a textbook created for this purpose, which presents problems first, with blank spaces for students to work them out. Discussion of the concepts and theory needed to understand and solve the problems, as well as the solutions, come later in the book. This book is referred to as the Reversed Textbook. Students attempt to answer questions or solve problems in class with instructor guidance as needed, before discussion of theory. Student learning in sections taught prior to implementing the Guided PBL method was compared with student learning in sections taught with the method. Results indicate that the approach motivated learning and improved student performance on a departmental final exam by an average of 9%. When measured on CT questions alone, the improvement was on average 24%. Finally, the Guided PBL approach also improved group task performance by 6%. All the improvements were statistically significant.